(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Diabetes is a chronic metabolic disorder affecting millions of people around the world with a huge socioeconomic. The current pharmacological agents used in diabetes therapy have several limitations and can cause side effects. As a result, researchers are exploring alternative to manage diabetes. In this study, researchers investigated the anti-diabetic efficacy of fish oil extracted from Coilia dussumieri in low dose streptozotocin-induced diabetic rats. The study aimed to determine the effect of fish oil consumption on pancreas. The group division of 48 rats into eight groups allowed for a comprehensive and detailed examination of the oil’s efficacy. The result of this study will contribute to the treatment of diabetes by shedding light on alternative therapies for diabetes management